Arthroscopic “V” Configuration Anatomic Reconstruction of Chronic Acromioclavicular Joint Dislocations Using Double-Bundled Autogenous Gracilis Tendon Graft Reinforced With FiberTape Internal Brace - Ayyappan V. Nair, D.Ortho, D.N.B., M.N.A.M.S.; Pramod Kumar Mohan, M.S. Ortho.; Ajit Jangale, M.S., M.R.C.S.; Pavan Krishna, M.S. Ortho.; Prince Shanavas Khan, D.Ortho, M.S. Ortho.; Maythilisharan Rambhojun, M.S. Ortho.; Sreejith Thampy, M.S. Ortho. (Arthroscopy Techniques)
We present an arthroscopic technique for chronic acromioclavicular joint dislocations that involves reconstructing the acromioclavicular and coracoclavicular ligaments using an autogenous gracilis tendon graft reinforced with FiberTape. We describe the technique using 2 tunnels in the clavicle and a coracoid tunnel to re-create the anatomic double-bundle coracoclavicular ligaments and also reconstruct the acromioclavicular ligament, providing both horizontal and vertical stability for the acromioclavicular joint. The advantage of our technique is the reduced use of implants and also providing stable reconstruction, a good chance for tendon integration into the coracoid, and fewer recurrences due to graft stretching, enabling good stability to the joint.